2023
DOI: 10.3390/foods12183397
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Poly (Lactic Acid)/Poly (Butylene Adipate-Co-Terephthalate)/Thermoplastic Starch Film Containing Salicylic Acid for Banana Preservation

Jian Ding,
Yi Hao,
Boqiang Liu
et al.

Abstract: Bananas are susceptible to the effects of endogenous enzymatic, leading to their rapid decay and deterioration. In order to mitigate economic losses and prolong the shelf life of bananas, the objective of this study was to develop a new and green gas-regulating packaging film. In this study, an active gas-regulating packaging film was prepared by extrusion, with mobil composition of matter (MCM)-41 loaded with salicylic acid (SA) as the active agent and poly (lactic acid) (PLA), poly (butylene adipate-co-terep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Ardjoum et al investigated the mechanical, thermal, and antimicrobial properties of PLA-based film enriched with Thymus vulgaris essential oil and an ethanolic extract of Mediterranean propolis and exhibited its potential as an active food packaging material [180]. PLA-, poly(butylene adipate-co-terephthalate)-, and starch-based films with salicylic acid were prepared and their potential as packaging for bananas was investigated by Ding et al [181]. The authors reported that the shelf-life of bananas could be extended by 4-5 days due to the excellent barrier and mechanical properties of the films [181].…”
Section: Homentioning
confidence: 99%
See 1 more Smart Citation
“…Ardjoum et al investigated the mechanical, thermal, and antimicrobial properties of PLA-based film enriched with Thymus vulgaris essential oil and an ethanolic extract of Mediterranean propolis and exhibited its potential as an active food packaging material [180]. PLA-, poly(butylene adipate-co-terephthalate)-, and starch-based films with salicylic acid were prepared and their potential as packaging for bananas was investigated by Ding et al [181]. The authors reported that the shelf-life of bananas could be extended by 4-5 days due to the excellent barrier and mechanical properties of the films [181].…”
Section: Homentioning
confidence: 99%
“…PLA-, poly(butylene adipate-co-terephthalate)-, and starch-based films with salicylic acid were prepared and their potential as packaging for bananas was investigated by Ding et al [181]. The authors reported that the shelf-life of bananas could be extended by 4-5 days due to the excellent barrier and mechanical properties of the films [181]. Hernandez-Garcia et al evaluated the effect of a multilayer PLA film on the shelf-life of fresh pork meat compared to commercial, high-barrier, multilayer packaging films.…”
Section: Homentioning
confidence: 99%
“…Recently, the need for biodegradable packaging materials has been growing in the storage of fruits to increase shelf-life. Especially, the combination of biodegradable polymers and bioactive natural molecules provides the fruit coating with multifunctionality such as gas regulating, antibacterial, and ultraviolet (UV) barrier properties. Despite the excellent barrier coating of fruits, biomass-based coating materials are still needed in terms of sustainable resources.…”
Section: Introductionmentioning
confidence: 99%